2009
DOI: 10.1177/0192623309335632
|View full text |Cite
|
Sign up to set email alerts
|

The Metrial Gland in the Rat and Its Similarities to Granular Cell Tumors

Abstract: Metrial glands are normal structures located in the mesometrial triangle of the pregnant rat uterus from gestational day (GD) 8 through termination of pregnancy. Metrial glands are composed of a dynamic mixed cell population of granulated metrial gland (GMG) cells, endometrial stromal cells, trophoblasts, blood vessels, and fibroblasts. Collections of similar cells may be seen in association with pseudopregnancy and other hormonal disturbances. Granulated metrial gland cells are the hallmark cell of the metria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
2
23
0
3
Order By: Relevance
“…The distribution of both perforinand IFN␥-positive cells was observed in the perivascular regions of the spiral arteries at both GD15.5 and GD18.5. Our observed perforin-positive cell staining was consistent with uNK cell/granulated metrial gland cell staining previously described in the rat placenta (Head et al, 1994;Picut et al, 2009;Sladek et al, 1998).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The distribution of both perforinand IFN␥-positive cells was observed in the perivascular regions of the spiral arteries at both GD15.5 and GD18.5. Our observed perforin-positive cell staining was consistent with uNK cell/granulated metrial gland cell staining previously described in the rat placenta (Head et al, 1994;Picut et al, 2009;Sladek et al, 1998).…”
Section: Resultssupporting
confidence: 91%
“…At GD14-15 initiation of trophoblast invasion into the decidua and large quantities of dispersed perforin-positive uNK cells are observed in the mesometrial triangle. In late gestation perforin-positive granulated metrial gland cells were mainly localized in the perivascular regions of the mesometrial triangle (Picut et al, 2009). At GD18, deep trophoblast invasion and a significant reduction of uNK cells are observed (Ain et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…After this period, at 14 DG there is a reduction in VEGF expression in all experimental groups, as we observed in this present study, which can be explained by a reduction in hypoxia, which also occurs physiologically (Plaisier 2011). Furthermore, from 14 DG, the decidua begins its regression (Picut et al 2009). Another important factor observed by Silva et al (2014) was the reduction of trophoblastic invasion of the maternal-fetal interface occurred in hypothyroid rats.…”
Section: Discussionsupporting
confidence: 82%
“…Granular cell tumor reacts positively in immunocytochemical stains for NSE, S-100 protein, and peripheral myelin proteins. In the female, it has been suggested that lesions termed granular cell tumors may in fact be normal or reactive metrial glands (Picut et al 2009). …”
Section: Neoplastic Proliferative Lesions: Accessory Sex Glands Intromentioning
confidence: 99%